Penerapan Metode User Centered Design (UCD) Pada Sistem Informasi Pemesanan Air Galon Tirta Berkah - Agnes Dwita Susilawati; Deddy Prihadi; Bei Harira Irawan (Universitas Muhammadiyah Sorong, 2023)
The increasing number of gallon water refill business competition makes these refilling entrepreneurs compete to improve the quality of their gallon refill services to customers, one of which is using online ordering services by customers, so that the job of refill officers who go around looking for empty gallons can be avoided. This research uses the User Centered Design (UCD) method in its development and is designed to be accessible online using PHP and MySQL database. where in this system in addition to producing an easy refill drinking water ordering system, how to order through the application can also generate automatic coupons for every purchase of refilled drinking water by customers and can exchange coupons with prizes systematically carried out by refill officers, so it is already no more forms of paper coupons that could be at risk of being lost or torn. The results of the iteration of adjusting system requirements to user needs are only carried out once, namely with the addition of a water price master data module.